HUBUNGAN SIKAP DAN PERAN PETUGAS KESEHATAN DENGAN PERILAKU DETEKSI DINI KANKER SERVIKS PADA AKSEPTOR KB - Eko Budi Santoso; Hasan Nidlom (Bajang Institute, 2025)
HPV or oncogenic Human Papilloma Virus, has a fairly high percentage in causing cervical cancer, which is around 99.7%. Cervical cancer is one of the most common cancers in women, the Surabaya City Health Office shows that the incidence of cervical cancer or cervical cancer decreases every year, namely in 2011 cervical cancer was 17.97%, in 2012 it was 17.13%, and in 2013 it fell to 14.31%. Then Based on the results of a preliminary study in June 2022 at Hospital X Surabaya, 16 patients with cervical cancer were obtained. This study was conducted to analyze the Analysis of Early Detection of Behavioral Cervical Cancer in KB Acceptors at Hospital X Surabaya, a retrospective analytical observational research design with a sample size of 43 respondents. The results of the study showed that variables related to Early Detection Behavior of Cervical Cancer based on the Chi-Square Test were knowledge (p value = 0.009), attitude (p value = 0.017), and the Role of Health Workers (p value = 0.004). The Health Service needs to prepare several materials, especially knowledge about Early Detection Behavior of Cancer, and periodically conduct health education.